Sudden sensorineural hearing loss: a case report supporting the immunologic theory Surdez neurosensorial súbita: relato de um caso clínico corroborando a teoria auto-imune - Antonio Luiz dos Santos Werneck; Luiz Carlos do Amaral Gurgel; Laurinda Moura de Mello; Gabriella Queiroz de Albuquerque (Arquivos de Neuro-Psiquiatria)
Sudden sensorineural hearing loss (SSNHL) is one of the autoimmune diseases of the inner ear (AIED), which is characterized by a hearing loss of above 30 decibels in at least three contiguous audiometric frequencies over a time course of 72 hours or shorter. Its cause can be found in only 10% to 15% of patients. Histopathologic findings have reported retrograde neuronal degeneration and atrophy of Corti's organ and of the vascular stria. This paper describes a case of a middle-aged female patient undergoing a treatment for hyperthyroidism who developed bilateral SSNHL. The patient was treated with methylprednilisone (1mg/kg/day) for three days with considerable hearing improvement. This treatment was followed by lung and kidney tuberculosis. The immune mechanism of this entity and the possibility of interconnected participation of the antigen type, of an autoimmune disease and of bacterial infection are discussed. A surdez neurosensorial aguda (SNSA) é uma das doenças auto-imunes do ouvido interno caracterizada pela perda da audição acima de 30 decibéis, em pelo menos 3 freqüências audiométricas contíguas, no período máximo de 3 dias. Sua causa só é definida em 10 a 15% dos pacientes. Achados histopatológicos demonstram degeneração neuronal retrógrada e atrofia do órgão de Corti e da estria vascular. Relatamos o caso de uma paciente de média idade em tratamento de hipertireoidismo que apresentou SNSA bilateral. A paciente foi tratada com metil-prednisilona (1mg/kg/dia) durante três dias evoluindo para uma melhora considerável da audição. Este tratamento foi seguido de tuberculose pulmonar e renal. Discute-se o mecanismo imunológico desta entidade, e a possibilidade de participação cruzada do tipo antígeno, doença autoimune e infecção bacteriana.